Educação na Amazônia: as experiências formativas e suas contribuições para a construção de saberes docentes para uma atuação política de gestores nas escolas municipais rurais do P.A. Nova Amazônia de Boa Vista-RR - Pereira, Kamilla Costa (Universidade Federal de Roraima, 2024)
This research aims to analyze in terms of training experiences of managers of rural municipal schools in the P.A. Nova Amazônia de Boa Vista-RR originated the construction of teaching knowledge necessary for political action in rural schools, in order to perceive the political dimension of teaching in Rural Education. The theoretical foundation is based on the interrelation of three central concepts: Training experiences, teaching action and social movements. The methodology is based on the principles of qualitative research and in terms of procedures, it is configured as documental and fieldwork. We surveyed the bibliography published in the form of books, articles published in periodicals (magazines), theses, conference proceedings, indexed in databases in online format that address the subject, with the purpose of building the theoretical framework that underlies the research. The field of research outside the two Municipal Rural Schools of the P.A. Nova Amazônia in Boa Vista/Roraima and was guided by the principles of Oral History, with open interviews with managers. Documents were also analyzed that showed the presence of a teaching action taken by praxis, such as: projects and albums. The interpretive analysis considered the social and political context of the rural space, as well as the urgencies of Rural Education, highlighting the social movements of rural men/women for land in the Amazon.